Event-by-event pT fluctuations and multiparticle clusters in relativistic heavy-ion collisions - Broniowski, Wojciech (2006)
We explore the centrality dependence of the pT correlations in the event-by-event analysis of relativistic heavy-ion collisions at RHIC made recently by the PHENIX and STAR Collaborations. We point out that the observed scaling of strength of dynamical fluctuations with the inverse number of the produced particles can be naturally explained by the formation of clusters. We argue that the large magnitude of the measured covariance implies that the clusters contain at least several particles. We also discuss whether the clusters may originate from jets. In addition, we provide numerical estimates of correlations coming from resonance decays and thermal clusters.